2020
DOI: 10.1111/jocn.15480
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' influence on consumers' experience of safety in acute mental health units: A qualitative study

Abstract: Aims and objectives: To explore how nurses influence the perceptions and experience of safety among consumers who have been admitted to an acute mental health unit. Background: Safety is a priority in acute mental health inpatient units, yet consumers do not always experience acute units as safe. Despite being primary stakeholders, little is known about what safety means for consumers in acute mental health units. Design: A qualitative descriptive study informed by naturalistic enquiry was conducted and is rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 42 publications
1
48
0
1
Order By: Relevance
“…The participants also emphasized how health professionals could enable or inhibit safety through their approach. Similarly, a recent Australian study found that therapeutic engagement with nurses was critical to fostering feelings of safety in mental health care (Cutler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The participants also emphasized how health professionals could enable or inhibit safety through their approach. Similarly, a recent Australian study found that therapeutic engagement with nurses was critical to fostering feelings of safety in mental health care (Cutler et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Risk focused approaches to safety in acute units promote safety for staff, but do not sufficiently recognise consumers' safety needs (Shepley et al., 2016). Not having nurses close by, for example, reduces consumers' feelings of safety in these units (Cutler et al., 2020), and lack of engagement by staff can exacerbate consumer aggression (Salzmann‐Erikson & Yifter, 2019). Aspects of the built environment have also been seen to influence consumers' perception of quality of care (Liddicoat et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The environment encompasses both the physical spaces of an acute unit and the social interactions and activities that occur within those physical spaces (Mollon, 2014). Other themes; Influence of Nurses (Cutler, Sim, Halcomb, Moxham, et al, 2020) and Being Seen as a Person (Cutler et al., 2020) are reported in separate papers due to the richness of the data.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity and depth of the data and the diversity of concepts explored in each key theme, they are reported separately (Cutler et al . 2020).…”
Section: Introductionmentioning
confidence: 99%